Dystrophic microglia in late‐onset Alzheimer's disease. Issue 4 (10th January 2020) - Streit, Wolfgang J.; Khoshbouei, Habibeh; Bechmann, Ingo
Abstract: Here, we summarize current understanding of functional involvement of microglial cells in the most common neurodegenerative disease to affect humans, which is sporadic or late‐onset Alzheimer's disease (LOAD). Our review narrowly focuses on insights obtained from post‐mortem neuropathological examinations of human brains paying particular attention to microglia as these cells have long been implicated as pivotal players in the cellular processes that lead to AD‐type neurodegeneration. Although complete understanding of the roles played by microglia in AD neurodegeneration remains elusive, our studies thus far have illuminated microglial involvement in LOAD, showing that microglial dystrophy, the morphological manifestation of senescence, can be integrated with other hallmark pathological features of AD, such as intraneuronal neurofibrillary degeneration (NFD) and extracellular deposits of amyloid‐beta (Aβ) protein. We have demonstrated an in situ correlation between microglial dystrophy and presence of NFD suggesting that neurodegeneration is secondary to aging‐related microglial deterioration, a concept founded on the notion that proper neuronal function is dependent on presence of healthy microglia. Diseased or weakened glia are detrimental for neuronal well‐being because their ability to provide neuronal support may be impaired. Our most recent work also links microglial dystrophy with Aβ deposits by showing that there is a chronic, yet futile microglial reaction to insoluble amyloid deposits. This inability of microglia to remove aggregated amyloid (a foreign body) causes microglial exhaustion and thereby exacerbates already ongoing aging‐dependent microglial deterioration. An eventual total loss of functional microglia in advanced LOAD promotes widespread NFD, dementia, and brain failure. Main Points: Microglial dystrophy increases in the aging human CNS and is widespread in LOAD. The extent of microglial dystrophy correlates with the extent of neurofibrillary degeneration. Dystrophy results from oxidative stress and immune exhaustion.